Impact of COVID-19 on pediatric surgical practice in Taiwan: a comprehensive analysis - Huang, Sheng-Yang; Chou, Chia-Man; Chen, Hou-Chuan (Frontiers in Pediatrics, 2024)
Background The COVID-19 pandemic has profoundly impacted global healthcare systems, causing significant disruptions in various medical practices. This study focuses on the specific effects of the pandemic on pediatric surgical practice in Taiwan, a region known for its effective public health measures and proximity to the initial outbreak. Methods The study analyzes data from January 2020 to August 2022, comparing it with historical records from January 2017 to August 2019. It examines changes in surgical case volumes, patient demographics, surgical indications, and trends in preoperative evaluations, surgical procedures, and postoperative care. Results The study reveals a decrease in total surgical cases from 2,255 to 1,931 during the pandemic. Notable findings include a slight increase in the average age of patients (4.81 to 5.10 years, p = 0.064), a significant shift in gender distribution towards male patients (68.9% to 73.5%, p = 0.0009), and changes in the types of surgical procedures performed, with head and neck and gastrointestinal surgeries seeing an increase. The average hospital stay lengthened, and certain specific surgical diseases, like hypospadias and liver tumors, showed an increase. However, the age distribution of pediatric surgical patients remained stable, and emergency surgical care was resiliently maintained. Discussion The findings demonstrate the adaptability of Taiwan's healthcare system in maintaining pediatric surgical care during the pandemic. The study highlights a significant gender disparity in surgical interventions and a shift towards more urgent and emergent care, reflecting the reorganization of healthcare services during this period. The study's limitations include its retrospective nature and focus on a single institution. Conclusion This research contributes valuable insights into the impact of the COVID-19 pandemic on pediatric surgical practice in Taiwan. It underscores the importance of adaptable healthcare strategies in ensuring continuity and quality of care during public health emergencies. Future research should focus on multi-institutional data and prospective studies to further understand these dynamics.